1976
DOI: 10.1002/j.1879-3479.1976.tb00567.x
|View full text |Cite
|
Sign up to set email alerts
|

Postpartum and Postabortion Sterilization

Abstract: Purandare, B. N. (Post-Graduate Institute (for Study and Research) in Gynaecology, Obstetrics, and Family Planning, Nowrosjee Wadia Maternity Hospital, Bombay 12, India). Postpartum and postabortion sterilization. Int J Gynaecol Obstet 14:65-70, 1976. To evaluate the feasibility of postpartum and postabortion sterilization, several studies (including unpublished data) from the India Fertility Research Programme and the International Fertility Research Program were reviewed. Within 36 hours of a term deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1978
1978
1995
1995

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Occasional reports suggest that PuTS may be associated with an increased risk of thrornbophlebitis and pulmonary embolus (due to coagulation and vascular changes), hemorrhage (due to increased vascularity of the uterus and adnexae), technical difficulties and failures (due to the large fundal and tubal size), uterine perforation with certain techniques (due to uterine distention and decreased wail strength), and increased risk of infection and wound complications during the early postpartum period [9]. In fact, the safety of PuTS is influenced by a number of factors, including: patient screening and selection, timing of the operation, type of anesthesia, surgical approaches, and tubal occlusion techniques, as discussed below.…”
Section: Safetymentioning
confidence: 98%
See 1 more Smart Citation
“…Occasional reports suggest that PuTS may be associated with an increased risk of thrornbophlebitis and pulmonary embolus (due to coagulation and vascular changes), hemorrhage (due to increased vascularity of the uterus and adnexae), technical difficulties and failures (due to the large fundal and tubal size), uterine perforation with certain techniques (due to uterine distention and decreased wail strength), and increased risk of infection and wound complications during the early postpartum period [9]. In fact, the safety of PuTS is influenced by a number of factors, including: patient screening and selection, timing of the operation, type of anesthesia, surgical approaches, and tubal occlusion techniques, as discussed below.…”
Section: Safetymentioning
confidence: 98%
“…An earlier study by Laros and Work [44] reported similar findings. Whether this was due to the possibly increased technical difficulties in successfully occluding the usually thicker and more vascular tubes immediately after delivery was not clear [9,43]. A recent university hospital-based report from Thailand reviewing 20 years of experience [45] reported a lower failure rate in PPTS (0.02%) than in InTS (0.19-0.20%).…”
Section: Puerperal Tubal Sterilization (Puts) Versus Interval Tubal Smentioning
confidence: 98%
“…However, more comparative clinical trials on the relative benefits among the commonly used tubal occlusion techniques for postpartum sterilisation (e.g. Pomeroy, tubal ring, clips) as well as evaluation studies of long term sequelae (such as incidence of ectopic pregnancy, subsequent hysterectomy, and other gynaecological procedures) are warranted (Purandare, 1976;Chick et al, 1985;Rioux, 1977).…”
Section: Discussionmentioning
confidence: 99%
“…T h e literature on this subject is inconclusive. Some studies have indicated that sterilization in this period does not significantly increase the complication or technical failure rates of the procedure (1,3,7), while another study has reported significantly higher complication rates (2).…”
Section: Discussionmentioning
confidence: 99%